2021
DOI: 10.1111/evo.14337
|View full text |Cite
|
Sign up to set email alerts
|

Two new hybrid populations expand the swordtail hybridization model system

Abstract: Natural hybridization events provide unique windows into the barriers that keep species apart as well as the consequences of their breakdown. Here, we characterize hybrid populations formed between the northern swordtail fish Xiphophorus cortezi and Xiphophorus birchmanni from collection sites on two rivers. We use simulations and new genetic reference panels to develop sensitive and accurate local ancestry calling in this novel system. Strikingly, we find that hybrid populations on both rivers consist of two … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(80 citation statements)
references
References 76 publications
(193 reference statements)
10
70
0
Order By: Relevance
“…Research on this sister species pair has shown that variation in local ancestry along the genome is best explained by the presence of prevalent hybrid incompatibilities (as opposed to historical effective populations size differences in the parental species or ecological drivers of ancestry variation; [35]), and has documented strong DMIs between them [23]. Here, we expand on our recent description of replicate hybrid populations of the species pair X. birchmanni ´ X. cortezi [46] to explore repeatability in local ancestry between these two types of hybrid populations.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Research on this sister species pair has shown that variation in local ancestry along the genome is best explained by the presence of prevalent hybrid incompatibilities (as opposed to historical effective populations size differences in the parental species or ecological drivers of ancestry variation; [35]), and has documented strong DMIs between them [23]. Here, we expand on our recent description of replicate hybrid populations of the species pair X. birchmanni ´ X. cortezi [46] to explore repeatability in local ancestry between these two types of hybrid populations.…”
Section: Introductionmentioning
confidence: 82%
“…birchmanni ´ X. cortezi are more deeply diverged than X. birchmanni ´ X. malinche (~450k generations diverged and ~250k generations diverged respectively) and unlike X. birchmanni and X. malinche, they do not differ in their time-averaged historical effective population sizes (Fig. S1) [46]. Hybrid populations between both species pairs formed recently (~100-150 generations ago [20,46]), likely due to human disturbance [47].…”
Section: Introductionmentioning
confidence: 97%
“…Powell et al (2021) measured mother-offspring ancestry differences to infer paternal ancestry, finding evidence for strong ancestry-based assortative mating in this system [consistent with other swordtail systems (Culumber et al 2014, Schumer et al 2017]. Using the mother-offspring data of Powell et al (2021), we calculate an ancestry correlation among mating pairs of 𝜌 = 0.928 (Methods; Fig. S8B).…”
Section: Cmentioning
confidence: 58%
“…In a hybrid population of the swordtail fish species Xiphophorus birchmanni and X. cortezi in Hidalgo, Mexico, genomic evidence suggests that the minor-parent ancestry (birchmanni) is deleterious to individuals of predominantly major-parent ancestry (cortezi) (Langdon et al 2021). Powell et al (2021) measured mother-offspring ancestry differences to infer paternal ancestry, finding evidence for strong ancestry-based assortative mating in this system [consistent with other swordtail systems (Culumber et al 2014, Schumer et al 2017]. Using the mother-offspring data of Powell et al (2021), we calculate an ancestry correlation among mating pairs of 𝜌 = 0.928 (Methods; Fig.…”
Section: Cmentioning
confidence: 99%
See 1 more Smart Citation